2003
DOI: 10.1016/j.jacc.2003.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amino-terminal pro-brain natriuretic peptide and accuracy of heart-failure diagnosis in primary care

Abstract: This study demonstrates that N-BNP measurement significantly improves the diagnostic accuracy of HF by GPs over and above customary clinical review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(43 citation statements)
references
References 31 publications
2
39
0
2
Order By: Relevance
“…A commonly used biochemical marker for severity of HF is pro-BNP, which has been shown to correlate with the severity of HF [24,25]. In the present study, the VO 2 peak/THV ratio was shown to correlate with pro-BNP, indicating that the ratio can potentially serve as a measure for severity of HF.…”
Section: Discussionsupporting
confidence: 60%
“…A commonly used biochemical marker for severity of HF is pro-BNP, which has been shown to correlate with the severity of HF [24,25]. In the present study, the VO 2 peak/THV ratio was shown to correlate with pro-BNP, indicating that the ratio can potentially serve as a measure for severity of HF.…”
Section: Discussionsupporting
confidence: 60%
“…A normal level of N-terminal pro-brain natriuretic peptide (NT-proBNP) effectively rules out left ventricular systolic dysfunction in outpatients presenting with symptoms possibly due to heart failure who are referred from primary care to hospital-based cardiology services [1,2,3,4]. Dyspnea is the leading symptom of heart and lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…The decision rule was derived from an individual patient data set from one of these studies (Zaphiriou et al 17 ) and externally validated on four others that included relevant variables. [18][19][20][21] The MICE rule comprised four clinical elements -Male, history of myocardial Infarction, Crepitations at the lung bases and oEdema -and was combined with natriuretic peptide levels to identify those likely to have heart failure and who should be referred for further diagnostic testing. The elements of the CDR are shown in Box 1.…”
Section: Clinical Decision Rulesmentioning
confidence: 99%